APLIKASI AUGMENTED REALITY PENGENALAN JENIS SAMPAH BERBASIS ANDROID - Kurniawan, Ferry; Annurrallah Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2022)
Augmented reality is a technology that combines images with the real world. Become a digital technology in socialization by using 3-dimensional objects displayed virtually through a smartphone. Dinas Lingkungan Hidup Kota Batam through the Pilah Sampah dari Rumah provides socialization about what waste can be made into compost, recycling and garbage that must be handled in a special way. Augmented reality technology to introduce virtual garbage without having to see the form of garbage directly. From this application can give education to the citizens to sort garbage from home.